PENCIPTAAN WAYANG GODHONK BERBAHAN LIMBAH DAUN KERING SEBAGAI UPAYA PENINGKATAN PENGETAHUAN SENI BUDAYA - Dr. Agus Purwantoro, M.Sn; Narsen Afatara; Soepono Sasongko; Jazuli Abdin Munib (Texture:Art and Culture Journal, 2021)
Traditional art is more hereditary and follows the existing standards, while modern art is more towards novelty and longs for fresh works. Creative artists will produce works that can be enjoyed both visually and conceptually. The art of wayang godhong performance is one of the mediums of expression about the traditions and lives of tobacco farmers in treading their lives. Wayang godhong is expected to be asustainable art and can also be included as contemporary art that combines tradition and contemporary art. Wayang godhong is indeed a unique and interesting work of art that combines performances and works of art that are embodied in the figures of the puppet forms. The works of art that are displayed become a puppet. Wayang godhong already has a lot of fans, besides that wayang godhong can also be used as an effective communication medium other than as a medium of education, especially knowledge of art and culture. In this study, the author uses an interactive art creation methodology with children, and effective two-way communication occurs so that art and culture knowledge education for children in Kalisak, Salaman, Magelang can be achieved.